2018
DOI: 10.3897/zookeys.727.20222
|View full text |Cite
|
Sign up to set email alerts
|

A review of the Madagascan pelican spiders of the genera Eriauchenius O. Pickard-Cambridge, 1881 and Madagascarchaea gen. n. (Araneae, Archaeidae)

Abstract: An endemic genus of Madagascan spiders (Araneae, Archaeidae, Eriauchenius) is revised. All 20 species of Eriauchenius are described and keyed, of which 14 are new species: Eriauchenius andriamanelo sp. n., Eriauchenius andrianampoinimerina sp. n., Eriauchenius goodmani sp. n., Eriauchenius harveyi sp. n., Eriauchenius lukemacaulayi sp. n., Eriauchenius milajaneae sp. n., Eriauchenius milloti sp. n., Eriauchenius rafohy sp. n., Eriauchenius ranavalona sp. n., Eriauchenius rangita sp. n., Eriauchenius rixi sp. n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…While A. paradoxa and M. antecessor have different somatic features, the morphology of the male pedipalps is conserved. This scenario is similar to what has been observed in the extant Madagascan "workmani-group" and the "vadoni-group", where genitalic differences are subtle, but non-sexual, somatic features, such as carapace shape and abdomen color, are distinct (Wood and Scharff 2018). The diagnostic features of Myrmecarchaea argue for monophyly of the genus, but the conserved genitalia suggest shared common ancestry for Myrmecarchaea and Archaea.…”
Section: Taxonomic Placement and Distributionsupporting
confidence: 81%
See 1 more Smart Citation
“…While A. paradoxa and M. antecessor have different somatic features, the morphology of the male pedipalps is conserved. This scenario is similar to what has been observed in the extant Madagascan "workmani-group" and the "vadoni-group", where genitalic differences are subtle, but non-sexual, somatic features, such as carapace shape and abdomen color, are distinct (Wood and Scharff 2018). The diagnostic features of Myrmecarchaea argue for monophyly of the genus, but the conserved genitalia suggest shared common ancestry for Myrmecarchaea and Archaea.…”
Section: Taxonomic Placement and Distributionsupporting
confidence: 81%
“…Decades later, extant species were discovered in the forests of Madagascar (Pickard-Cambridge 1881), and then were also found and documented from South Africa and Australia (Forster and Platnick 1984). The number of extant species contin-ues to grow due to taxonomic revision, some recent (e.g., Lotz 2015;Wood and Scharff 2018). Yet thus far, the extant clades remain known only from these three areas.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on invertebrates have emphasized the importance of mountain or rainforest refugia (Wesener et al 2011;Wood et al 2015) and pointed out that in-situ speciation in such refugia, together with time and adaptive niche radiation, has been fundamentally important in diversification. Many taxonomic revisions have also focused on taxa that are exclusively or predominantly found in the high-altitude forests of the east (Griswold 1997;Griswold et al 2012;Wood and Scharff 2018) and documented substantial microendemism. For more arid habitats, a study by Wesener (2009) found that endemism in pill millipedes from dry forests was not as pronounced as that of species occurring in mesic habitats.…”
Section: Biogeographymentioning
confidence: 99%
“…In the past two decades, there has been major progress in documenting the Malagasy invertebrate fauna at the taxonomic level, including many arachnid lineages (e.g., Griswold et al 2012;Saucedo et al 2015;Wood and Scharff 2018). Several studies have addressed patterns and causes of invertebrate speciation (e.g., Miraldo et al 2011;Wesener et al 2011;Agnarsson et al 2015), but no data are presently available for pseudoscorpions, a mesodiverse arachnid lineage, following the more diverse spiders and mites, which are found in all ground habitats on Madagascar (WPC 2022).…”
Section: Introductionmentioning
confidence: 99%